2021
DOI: 10.1186/s12877-021-02552-9
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among whole-body skeletal muscle mass, masseter muscle mass, oral function, and dentition status in older Japanese adults

Abstract: Background Generalized loss of skeletal muscle mass (SMM) may modulate or otherwise affect the loss of masseter muscle mass and be responsible for low masseter muscle performance and strength (i.e., low oral function). Moreover, dentition status can affect oral function independent of the muscle state. This cross-sectional study aimed to simultaneously investigate the relationships among whole-body SMM, masseter muscle mass, oral function (masseter muscle performance and strength), and dentitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Therefore, for the purpose of static measurement of body composition, including skeletal muscle mass, body composition analyzer was used un this study. InBody, which is a multifrequency impedance measurement method, has been widely applied in clinical research because it shortens the time required while measuring a large amount of information by simultaneous direct multifrequency measurement of body area (17,36,37) , and it has been reported to be highly accurate (38,39) . Although body fat mass increases with age (11) , it has been reported that the percentage of it and lean body mass decrease in the older adults (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for the purpose of static measurement of body composition, including skeletal muscle mass, body composition analyzer was used un this study. InBody, which is a multifrequency impedance measurement method, has been widely applied in clinical research because it shortens the time required while measuring a large amount of information by simultaneous direct multifrequency measurement of body area (17,36,37) , and it has been reported to be highly accurate (38,39) . Although body fat mass increases with age (11) , it has been reported that the percentage of it and lean body mass decrease in the older adults (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study published in 2021, reported that low skeletal muscle mass was associated with poor oral function due to low masseter muscle mass [15]. Additionally, the direct effects of the number of functional teeth on maximum occlusal was reported using a structural equation modelling strati ed by sex [15]. Muscle mass percentage in men and women were different in the physical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…According to an earlier community-survey for those aged ≥ 65 years elucidating the relationship between the frailty and oral function, the lower muscle mass index and masseter muscle thickness was reported in the frail rather than in robust elders [12]. Moreover, another study published in 2021, reported that low skeletal muscle mass was associated with poor oral function due to low masseter muscle mass [15]. Additionally, the direct effects of the number of functional teeth on maximum occlusal was reported using a structural equation modelling strati ed by sex [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study, nevertheless, suggests that M-CSA is not as robust a prognostic indicator as PLVI in these patients. Furthermore, localized masseter muscle atrophy can occur in patients with tooth loss, dental prosthesis or other causes for reduced masticatory function [9,18,19]. Caution needs to be exercised in using it as a surrogate for global muscle deconditioning.…”
Section: Discussionmentioning
confidence: 99%